From state-centric organizational articulations to neighborhood community networks: case analysis in Talca, Chile - Letelier Troncoso, L. Francisco.; Paredes, Juan Pablo; Fernández González, Víctor.; Adasme, Benjamín; Tapia Barría, Verónica. (Universidad Nacional de Rosario. Facultad de Humanidades y Artes, Escuela de Historia, 2023)
This article compares two neighborhood community processes that have taken place in an intermediate city in central Chile. The first of these took place before the social outbreak of 2019 and the second originated from it. In both cases, there are articulations and links that, on the one hand, go beyond the political-administrative limits established by the dominant way of conceiving the neighborhood and, on the other, complicate community agendas. However, there are important differences between them. In the first, pre-outbreak, a state-centric process is appreciated: the efforts of the articulation are oriented to the search for a response from the state. In the second, post-outbreak, the process is rather socio-centric: efforts are aimed more at strengthening the community networks themselves and their autonomy. This socio-centric process and reticular and performative one, opens up new possibilities for thinking about the neighborhood. Although the experiences that we had studied before show an increase in the power of organizations to mediate, this is still subject to state ways of managing the social. Instead, here the community appears as an autonomous sphere: it does not exist to address the state, but to reproduce itself.
De articulaciones organizacionales estado-céntricas a entramados comunitarios vecinales: análisis de casos en Talca, Chile
Keywords: Neighborhood process; Politicization; Social outbreak; Territorial articulation; Comunidad